Whole-Exome Sequencing in Idiopathic Short Stature: Rare Mutations Affecting Growth - Noorian, Shahab; Khonsari, Nami Mohammadian; Savad, Shahram; Hakak-Zargar, Benyamin; Voth, Tessa; Kabir, Koroush (Journal of Pediatric Genetics, 2020)
Idiopathic short stature (ISS) is a common diagnosis of exclusion in patients with short stature (SS). In this article, we aimed to identify the genetic causes of SS in patients with ISS and investigate treatment options. Fourteen children with diagnosis of ISS were identified, and whole-exome sequencing (WES) was subsequently conducted on blood-derived DNA. Five patients were correctly diagnosed with ISS and four had rare mutations that have not been previously reported. Four patients had mutations known to cause SS and one had a mutation that was known not to affect height. WES can help identify rare mutations implicated in ISS.
Keywords: idiopathic short stature; medical; whole-exome sequencing